The death debates: a call for public deliberation - Rodríguez-Arias, D; Véliz, C (Wiley, 2013)
In this issue of the Report, James L. Bernat proposes an innovative and sophisticated distinction to justify the introduction of permanent cessation as a valid substitute standard for irreversible cessation in death determination. He differentiates two approaches to conceptualizing and determining death: the biological concept and the prevailing medical practice standard. While irreversibility is required by the biological concept, the weaker criterion of permanence, he claims, has always sufficed in the accepted standard medical practice to declare death. Bernat argues that the medical practice standard may be acceptable on the ground that proving circulatory or brain permanence is sufficient to assure complete accuracy for death diagnosis. The topic requires public deliberation: processes to survey people's opinions and mechanisms to channel their opinions into policy‐making. What is at stake is the nature of our society. Do we want an expertocracy, in which an enlightened few design policies for the greater good of the majority and exploit the lack of public knowledge to achieve compliance?